Measuring criminal attributions with a normative instructional set: is there a difference? - Kroner, Daryl G. (Legal and criminological psychology, 2006)
1Purpose. The purpose of this study was to evaluate the utility of the Criminal Attribution Inventory's (CRAI) normative instructional set (respondent's perception of the average type of crime) in assessing criminal attributions. Methods. To determine the role of the CRAI's instructional set, a content-equivalent, personal instructional CRAI set was created. Correlations with an established criminal attribution scale (Blame Attribution Inventory [BAI]) and a measure of socially desirable responding (Paulhus deception scales [PDS]) were calculated. Partial correlations between the CRAI and BAI, controlling for the personal instructional CRAI, were calculated. Partial correlations were also calculated between the personal instructional CRAI and the BAI, controlling for socially desirable responding. Results. The normative instructional CRAI assessed similar domains as the personal instructional CRAI and made an additional contribution to criminal attributions. Socially desirable responding was minimally related to the normative instructional CRAI and could not account for the differences between the normative and personal instructional CRAI sets. Conclusions. The CRAI's normative instructional set assesses personal criminal attributions within the external blame domain assessing unique attributional variance. Such an instructional set has utility in assessing criminal attributions among those offenders who deny their offences.